PERSEPSI MASYARAKAT TERHADAP PEMBANGUNAN JARINGAN GAS RUMAH TANGGA DI DESA GAS ALAM KECAMATAN MUARA BADAK KABUPATEN KUTAI KARTANEGARA - Wahyuddin; Fahleti, Widya Hana (SEKOLAH TINGGI ILMU EKONOMI TENGGARONG, 2022)
One of the government's programs in seeking alternative energy is the construction of a household gas network that has been running from 2017 to the present. One area that has received a household gas network is Gas Alam Badak Village in Muara Badak, Kutai Kartanegara. The success of the development carried out by the government cannot be separated from the perceptions of the surrounding community, both those who accept it or reject it. This study aims to determine people's perceptions of the construction of household gas networks in Gas Alam Village, Muara Badak, Kutai Kartanegara. This type of research is quantitative descriptive, with a total population of 1,117 households while the sample is 168. The results of the study were seen from the cognitive, affective, and evaluative aspects of the Gas Alam Village community to support the household gas network program.Â